(untitled) (Bangladesh Pharmaceutical Journal, 2020)
The current study was designated to explore the antioxidant and antibacterial properties of the methanolic extract of Magnolia champaca stem bark and its different fractions. Antioxidant activity was assessed using total antioxidant capacity, ferric reducing power, DPPH, hydroxyl and hydrogen peroxide scavenging assay. Antibacterial activity was evaluated against five gram positive and five gram negative bacteria using disc diffusion assay method. Among the different fractions, chloroform fraction (CHF) and ethyl acetate fraction (EAF) showed the highest antioxidant activity whereas aqueous fraction (AQF) showed lowest activity in DPPH radical scavenging assay with IC50 of 12.12, 22.41 and 55.16 μg/ml, respectively. Both of the extracts CHF and EAF also exhibited highest total antioxidant capacity, ferric reducing power and hydrogen peroxide scavenging activity with concentration dependent manner when compared to standard BHT. Moderate to potent antibacterial activity was observed against all tested organisms compared to standard azithromycin. The results from the present study revealed that the different fractions of stem bark of M. champaca specially CHF and EAF possess antioxidant and antibacterial property which support its use in traditional medicine and suggesting that the plant may be further investigated to discover its pharmacologically active natural products. Bangladesh Pharmaceutical Journal 23(2): 96-102, 2020